Reading comprehension : - Blachowicz, Camille L. Z. (Guilford Press, 2008)
The authors offer specific classroom practices that help K-9 students compare and evaluate print and online sources, develop vocabulary, build study and test-taking skills, and become motivated readers. The second edition reflects new research on informational literacy and academic and content-specific vocabulary development, and also discusses the impact of recent federal initiatives.